IWAKU: NEWS AND MARKETPLACE APPLICATION BASED ON ANDROID TO MAXIMAZE FISHERIES SECTOR SECTOR DEVELOPMENT - Setiawan, Islamudin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to educate the fishermen on a median basis through IWAKU application media using IWAKU applications of fishermen and fish farmers can get information about fish from the nursery stage until the enlargement. Through this media the authors hope the fishermen and fish farmers can increase fish production or fish catch in the sea. This study uses the lean startup method commonly used in building startup in the early stages.The benefits of this study indicate that the fish sector has enormous potential especially in Indonesia, if there is a new innovation in this fish sector it will be very helpful in maximizing the potential, through IWAKU will provide the most complete news portal about fish and make IWAKU as a fish marketplace.Keywords: IWAKU, Startup, Application, News, Fish Marketplace, Fish Potential